Spontaneous pneumomediastinum in previously healthy pediatric patients: A case series - Isabel Cristina Brito Rojas; Mayra Angelica Hernandez Peñuela; Martin Alfonso La rotta; Vanessa Medina Gaviria (Elsevier, 2024)
Introduction: Spontaneous pneumomediastinum is defined as the presence of air in the mediastinum not associated with trauma or iatrogenic causes. This pathology is rare in the pediatric population. Cases presentation: Case 1: A previously healthy 15-year-old male was admitted with a 5-day history of sudden-onset chest pain associated with odynophagia. Upon admission, there were no signs of respiratory distress, but slight subcutaneous emphysema in the neck. A neck X-ray demonstrated extensive prevertebral and paracervical air. Chest x-ray showed increased transparency and delineation of the mediastinal contours as well as increased retrosternal space, all compatible with pneumomediastinum. Chest CT showed extensive emphysema of the supra- and infrahyoid anterior neck bilaterally. Neither the esophagram nor the upper endoscopy reveal an esophageal lesion. The patient remained stable without the need for supplemental oxygen, started a liquid diet 72 hours post admission with adequate tolerance, and was discharged home on the fourth day of hospitalization. Case 2: A previously healthy 10-year-old female was admitted to the emergency department with a clinical picture of odynophagia that prior to admission was associated with signs of respiratory distress and desaturation. Chest X-ray showed subcutaneous emphysema in the left cervical, thoracic, and axillary regions. Chest CT scan with oral contrast showed emphysema of the soft tissues of the left chest wall and neck and no extravasation. Upper endoscopy showed no lesions in the upper digestive tract. She resumed oral feedings 2 days post admission and was discharged home 6 days post admission. Conclusion: Spontaneous pneumomediastinum is an infrequent benign clinical entity in children, especially in those with no history of lung disease, infections or substance abuse. Conservative treatment is successful in most cases. Rapid reinitiation of oral feedings does not increase complications and allows an early discharge.